Copper-Catalyzed Synthesis of 1,2,4-Triazoles via Sequential Coupling and Aerobic Oxidative Dehydrogenation of Amidines - Xu, Hao; Jiang, Yuyang; Fu, Hua (Synlett, 2013)
A convenient, efficient, and practical copper-catalyzed one-pot method for the synthesis of 1,2,4-triazoles has been developed via reactions of amidines. The procedure underwent sequential base-promoted intermolecular coupling (nucleophilic substitution) between two amidines and intramolecular aerobic oxidative dehydrogenation, and the inexpensive, convenient, and efficient method for the synthesis of 1,2,4-triazoles will attract much attention in academic and industrial research.
Keywords: copper; aerobic oxidative; dehydrogenation; amidines; 1,2,4-triazoles